1997
DOI: 10.1046/j.1440-169x.1997.t01-2-00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C induces cortical granule exocytosis in a Ca2+‐independent manner, but not the resumption of cell cycle in porcine eggs

Abstract: The effects of protein kinase C (PKC) activation on meiotic resumption and cortical granule (CG) exocytosis as well as its dependence on Ca2+ in porcine eggs matured in vitro were studied. Cortical granule release was judged by both confocal laser microscopy after the eggs were labeled with fluorescein isothiocyanate-peanut agglutinin (FITC-PNA) and electron microscopy. Meiotic resumption and pronuclear formation were observed after eggs were stained with acetic orcein. When eggs were treated with PKC activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
3
16
2
Order By: Relevance
“…The exocytosis of cortical granules does not always accompany oocyte activation by artificial activating stimuli, and this was the case, for example, when activation had been induced by the inhibition of protein kinases (Mayes et al, 1995). These observations are in agreement with those of Sun et al (1997), who proved that the activation of oocytes and the exocytosis of cortical granules were independent processes. Quite a long exposure to an NO-donor (10 hours) is necessary for the activation of pig oocytes.…”
Section: Does Nitric Oxide Activate Mammalian Oocytes?supporting
confidence: 86%
See 1 more Smart Citation
“…The exocytosis of cortical granules does not always accompany oocyte activation by artificial activating stimuli, and this was the case, for example, when activation had been induced by the inhibition of protein kinases (Mayes et al, 1995). These observations are in agreement with those of Sun et al (1997), who proved that the activation of oocytes and the exocytosis of cortical granules were independent processes. Quite a long exposure to an NO-donor (10 hours) is necessary for the activation of pig oocytes.…”
Section: Does Nitric Oxide Activate Mammalian Oocytes?supporting
confidence: 86%
“…Fan et al (2002b) demonstrated a change in the localization of PKC -α, -β I , -γ in maturing porcine oocytes and after their activation. On the other hand, Sun et al (1997) did not observe metaphase II transition and meiosis resumption in mature porcine oocytes after PKC stimulation, which indicates that PKC does not trigger these processes. Green et al (1999) reported that PKC inhibition together with protein kinase A and myosin light chain kinase inhibition resulted in the activation of the porcine oocyte.…”
Section: Which Signalling Cascades Remained Silent In No-induced Oocymentioning
confidence: 72%
“…Fan et al (2002b) demonstrated a change in the localization of PKC-α, -β I , -γ in maturing porcine oocytes after their activation. On the other hand, Sun et al (1997) did not observe any metaphase II transition and meiosis resumption in mature porcine oocytes after PKC stimulation, which indicates that PKC does not trigger these processes. Green et al (1999) reported that PKC inhibition, together with protein kinase A and myosin light chain kinase inhibition, results in the activation of porcine oocyte.…”
mentioning
confidence: 70%
“…The PKC activity itself is insufficient for the activation of porcine oocytes (Sun et al, 1997;Fan et al, 2002b). However, its activity is necessary for complete oocyte activation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the PKC-z, -l, -t isotypes belong to the atypical PKCs (aPKCs) and are independent of both Ca 21 and DAG (Liu and Heckman, 1998). The role of PKC activation in the exit from metaphase II of porcine oocytes has been studied using PKC-activators such as phorbol-12-myristate-13-acetate (PMA: an activator of all isotypes of PKC; Sun et al, 1997;Ito et al, 2003) and 1-oleoyl-2-acetylglycerol (OAG: an activator of calcium-dependent PKC isotypes; Sun et al, 1997). After oocyte treatment and their cultivation for an additional 20 h, the female pronucleus was not observed either with PMA or with OAG .…”
mentioning
confidence: 99%